2001
DOI: 10.1136/ard.60.10.928
|View full text |Cite
|
Sign up to set email alerts
|

Values for function in rheumatoid arthritis: patients, professionals, and public

Abstract: Background-Although many disability questionnaires measure fact very eYciently, they do not allow for consideration of the relevance of that disability to the patient. Data suggest that professionals misinterpret the relevance of disability for the patient and thus, also, the outcome of treatment. Objectives-Firstly, to examine agreement on levels of importance for the items on a validated disability scale (Health Assessment Questionnaire (HAQ) and Modified HAQ (MHAQ)), within groups of patients with rheumatoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 31 publications
3
69
0
1
Order By: Relevance
“…In the same manner, quantitative studies have investigated patient priorities among the HAQ items and demonstrated that priorities differed [9] with rather low agreement between persons with RA (weighted Îș = 0.241) [8]. Interestingly, no HAQ item seems to be unimportant to all persons with RA [15].…”
Section: The Literature Provides a Similar Picture Of Haq Deficienciesmentioning
confidence: 99%
“…In the same manner, quantitative studies have investigated patient priorities among the HAQ items and demonstrated that priorities differed [9] with rather low agreement between persons with RA (weighted Îș = 0.241) [8]. Interestingly, no HAQ item seems to be unimportant to all persons with RA [15].…”
Section: The Literature Provides a Similar Picture Of Haq Deficienciesmentioning
confidence: 99%
“…Although primarily focusing on ability, research using the valued life activities instrument has addressed the relative importance of different activities [39]. Also, researchers relating to the HAQ [23] or the ICF model [26] have discussed whether the perceived importance of activities should be included in assessments. In RA patients, declines in the ability to engage in recreational activities and social interactions are related to the onset of depressive symptoms [39], which may in its turn influence participation in work.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to individual aspects of functioning such as body functions and an individual's ability to perform certain activities, the ICF model includes participation which is the actual performance of activities in a social context. Regarding the ability of the individual, several assessment instruments have been developed and within a psychometric perspective it has been possible to make selections of items because many abilities correlate fairly well with each other [21,[23][24][25][26]. However, it is more difficult to know how participation in work should be assessed in order to understand and prevent work disability; it is not clear what categories within the ICF activity/participation component that have to be considered when relating participation to e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the WTP method is its ability to separately emphasize the different functions in the HAQ. It has been found in earlier studies that health care professionals and RA patients emphasize different issues in the treatment outcomes [11,14]. The significance of, for instance, pain and functional deficits also differ among the patients during the different stages of the disease [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the function with worst functional capacity in each domain is used in forming the HAQ index, which may distort the actual functional capacity. It has been suggested that a tool parallel to HAQ would be developed, which would measure how the patients value different functions and would provide weighted values for the different functional deficits [11,14]. Monetary value is a concrete way of portraying subjective valuation and could be a starting point for the creation of such a tool.…”
Section: Discussionmentioning
confidence: 99%